From Panorama to Parking Garage: An Architectural and Archival History of the Toronto Cyclorama - Gapp, Isabelle; Mace, Jessica (Imaginations, 2024)
This text presents an architectural and archival history of the Toronto Cyclorama, built 1887 and demolished in 1976. Through an examination of its genesis and changing uses over time—as a cyclorama, machine hall, then parking garage—the text unveils its history, situating it within the scope of Toronto’s architectural heritage and North American cyclorama buildings. With this text, the authors also champion the study of all kinds of local art and architecture rather than just those deemed to have superlative qualities, and provide a case study for the value of adaptive reuse and its inclusion in architectural histories.